2012
DOI: 10.1136/thoraxjnl-2012-202678.241
|View full text |Cite
|
Sign up to set email alerts
|

P180 Aetiology of Bronchiectasis in a Non-Specialist Service. How Does COPD Affect the Picture?: Abstract P180 Table 1

Abstract: Poster sessions A142Thorax 2012;67(Suppl 2):A1-A204Prescription refill data were used to calculate percentage adherence by dividing the amount collected by the amount prescribed, multiplied by 100. Participants were categorised as adherent (score≥80%) and non-adherent (score<80%) to inhaled antibiotics and other respiratory medicines using this method. Participants completed the modified Self-reported Medication-taking Scale for ACT (score 0-5; adherent score≥4, non-adherent score<4). Spirometry was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Upon further review, 6201 abstracts or articles were rejected for meeting the study exclusion criteria (design not an observational study or no non‐cystic fibrosis bronchiectasis patients enrolled). Of the 306 full‐text articles reviewed at Level II screening, 54 reported on aetiologies of bronchiectasis . The reference lists of included studies were manually reviewed for identification of relevant articles that were not identified from the initial search.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon further review, 6201 abstracts or articles were rejected for meeting the study exclusion criteria (design not an observational study or no non‐cystic fibrosis bronchiectasis patients enrolled). Of the 306 full‐text articles reviewed at Level II screening, 54 reported on aetiologies of bronchiectasis . The reference lists of included studies were manually reviewed for identification of relevant articles that were not identified from the initial search.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of the identified aetiologies ranged from 18% to 95%. Geographically, 62.5% of aetiologies ( n = 35) were reported in studies conducted in Europe, 14.3% ( n = 8) in Asia, six in Oceania (Australia), five in South America (Brazil), one in North America (USA) and one in Africa (Tunisia)…”
Section: Resultsmentioning
confidence: 99%